2013
DOI: 10.5114/aoms.2013.33173
|View full text |Cite
|
Sign up to set email alerts
|

– Anatomical pathology Sexual dimorphism of the suprascapular notch – morphometric study

Abstract: IntroductionThe concept of the study was to compare the morphometry of the suprascapular notch (SSN) in females and males because its size and shape may be a factor in suprascapular nerve entrapment.Material and methodsThe measurements of 81 scapulae included morphological length and width, maximal width and length projection of the scapular spine, and width and length of the glenoid cavity. The width-length scapular and glenoid cavity indices were calculated. In addition to standard anthropometric measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…But no significant sexual differences were established in our study. According to the results of Polguj et al [27], the distribution of the SSN types in both sexes was similar too. Albino et al [1] concluded in their study that the type of the SSN is not related to the sex and age of the individuals.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…But no significant sexual differences were established in our study. According to the results of Polguj et al [27], the distribution of the SSN types in both sexes was similar too. Albino et al [1] concluded in their study that the type of the SSN is not related to the sex and age of the individuals.…”
Section: Discussionmentioning
confidence: 74%
“…Albino et al [1] concluded in their study that the type of the SSN is not related to the sex and age of the individuals. As far as the completely ossified superior transverse ligament is concerned, Polguj et al [27] established that it was more frequent in females than in males (9.1% vs. 4.9%). Our results confirm the more common ossification of the superior transverse ligament in the female scapulae, because we did not observe it in any of the male bones.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, morphometric values of the scapula were also different between races (Taser and Basoglu, 2003). A statistically significant difference was observed in scapular length, scapular width, maximum length of the spine, infraspinous vertebral border, medial supraspinous border, infraspinous axial border, lateral supraspinous border, glenoid cavity height, glenoid cavity width and scapular index values of the fox scapula in terms of genders and values were higher in males than in females as for human beings and fox (Welsch et al, 2003;Polguj et al, 2013;Felska-Blaszczyk et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
“…In this study, the scapular length, scapular width, maximum length of the spine, infraspinous vertebral border, medial supraspinous border, infraspinous axial border, lateral supraspinous border, glenoid cavity height, glenoid cavity width (Fig. 1-2) and angulus cranialis, caudalis and ventralis were measured from 3D model of the scapula depending on the literature (Welsch et al, 2003;Hoenecke et al, 2010;Zhang et al, 2012;Sangam and Devi, 2014;Bryce et al, 2008;Wells, 2009;Polguj et al, 2013;Moineau et al, 2012;Felska-Błaszczyk et al, 2013;Badr El Dine and Hassan, 2016) and the scapular index (scapular width× 100/ scapular length) as well as the glenoid index (glenoid cavity width× 100/ glenoid cavity height) were obtained from these measurements. The statistical analysis was performed via SPSS 15.0 windows software program.…”
Section: Methodsmentioning
confidence: 99%
“…Shi et al [ 41 ] confirmed that there is excellent side-to-side symmetry in glenoid shape regardless of sex. Moreover, Polguj et al [ 32 ] note that the distribution of the suprascapular notch types is similar between the two sexes. Sexual dimorphism was further investigated by Polguj et al [ 33 ] on total of 616 computer tomography scans of shoulders randomly selected from the database of patients who were being investigated due to chest problems.…”
Section: Discussionmentioning
confidence: 99%